Open-Ended Approach as a Development of Imaginative Creativity in Learning History - Amanullah, Muhammad Abror; Putro, Rendy Wahyu Satriyo; Supriatna, Nana (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This study discusses Open-Ended questions by relying on questions that are stimulating and encourage students in learning history to imagine the question "If" on historical content or historical material, or with the question "How and Why" to be applied in history learning in high school and college. Some of these questions can be a trigger for students and college students to reflect and imagine the material of historical figures and historical events in the past by utilizing the creativity and imagination of students and college students in learning history. So, in learning history, students and college students give more meaning to historical events and historical figures in the historical material that has been delivered in class. So that learning history is more interesting and explores the potential of historical material more deeply and in detail.